Differentiated Learning Assisted by Digital STRIP Comic Media Improves Elementary School Student Learning Outcomes - Safitri, Insan; Nurharini, Atip (Universitas Pendidikan Ganesha, 2024)
The obstacle in learning activities is that students do not need to understand the learning material, so they get low learning outcomes. Based on this, this research aims to analyze the influence of differentiation learning assisted by digital STRIP comic media on the learning outcomes of elementary school students. The type of research used in this research is quantitative research with quasi-experimental research as the research design. This research uses a quasi-experimental research design. The population in this study was 38 students. A random method was used to determine the sample for this research. The methods used to collect data are interviews, observation, documentation, questionnaires, and tests. The instruments used to collect data were questionnaire sheets and test questions. The technique used to analyze data is inferential statistical analysis. The results of the research are that there are differences in student learning outcomes in the experimental class, which uses differentiated learning assisted by comic strip media, compared to the control class, which uses conventional learning. The results of the n-gain test show that the average score of the control class is in the less effective category, and the experimental group is in the moderate effectiveness category. It was concluded that the differentiation learning model assisted by digital STRIP comic media could improve elementary school students' learning outcomes.